Birds in the Rock Art of Gawilgarh Hill - Himanshu M. Mahajan; Ashikkumar Nagwanshi; Prabash Sahu (The Bioscan, 2026)
The rock art of Gawilgarh Hill, situated in the Satpura ranges of central India, constitutes a significant assemblage of prehistoric imagery that highlights the ecological presence and cultural significance of fauna in early human societies. Among the various animal depictions, avian figures are prominently featured in frequency and symbolic expression.